Does it pay to patent green innovations?: stock market reactions to family and nonfamily firms' green patents - Chirico, Francesco (Journal of business ethics, 2025)
Are green patents granted to family firms perceived more favorably by the market than those granted to non-family firms? Using a sample of 8918 green patents granted to family and non-family firms between 2014 and 2018, our study shows that it depends on the attributes of the green patent. Integrating the green innovation and family firm literatures with signaling theory, we develop a theoretical framework that highlights the need for family firms to balance their pursuit of green innovation with signals of innovation stability and due diligence so as to gain the greatest market value from their green patents. In contrast, we theorize that green patents offer nonfamily firms the greatest gain in market value when they signal innovation radicalness and newness. While our results show that the stock market reaction does not vary significantly between family and non-family firms, when we consider the attributes of green patents, we find that compared to nonfamily firms, family firms with longer green patent grant lags realize a more positive market reaction whereas those with higher patent radicalness experience a more negative market reaction. As such, our study suggests that the types of green patents that garner the greatest market value differ for family and nonfamily firms. The findings are robust to alternate family firm definitions, and additional robustness checks.